(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Speech characterizes the level of general development and culture of a person. For the pedagogical process as a whole, speech activity is an important component. It is realized in any activity, takes part in its organization and functioning. This article discusses the role of professional speech in the process of teaching students of the philological direction.